Oracle Exadata Survival Guide - Fitzjarrell, David; Spence, Mary Mikell; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Oracle Exadata Survival Guide is a hands-on guide for busy Oracle database administrators who are migrating their skill sets to Oracle's Exadata database appliance. The book covers the concepts behind Exadata, and the available configurations for features such as smart scans, storage indexes, Smart Flash Cache, hybrid columnar compression, and more. You'll learn about performance metrics and execution plans, and how to optimize SQL running in Oracle's powerful, new environment. The authors also cover migration from other servers. Oracle Exadata is fast becoming the standard for large installations such as those running data warehouse, business intelligence, and large-scale OLTP systems. Exadata is like no other platform, and is new ground even for experienced Oracle database administrators. The Oracle Exadata Survival Guide helps you navigate the ins and outs of this new platform, de-mystifying this amazing appliance and its exceptional performance. The book takes a highly practical approach, not diving too deeply into the details, but giving you just the right depth of information to quickly transfer your skills to Oracle's important new platform. Helps transfer your skills to the platform of the future Covers the important ground without going too deep Takes a practical and hands-on approach to everyday tasks
Keywords: Computer science; Database management; Computer Science; Database Management; Data Storage Representation